PERAN MARKETING COMMUNICATION, SOCIAL MEDIA SPECIALIST, DAN DATA ANALYST DALAM STRATEGI BRAND COMMUNICATION UNTUK MENINGKATKAN BRAND AWARENESS DAN BRAND ENGAGEMENT MAMI AYAM POP MELALUI KAMPANYE "FLAVOR AND TUNES POP" - Nevi Aulia Agatha Rasjid; Adi Nugroho (Interaksi Online, 2026)
Mami Ayam Pop is a culinary MSME in Semarang City specializing in Ayam Pop. However, a survey involving 202 respondents showed that brand awareness and understanding of the brand positioning remained low. This study aims to analyze the implementation of a brand communication strategy through the "Flavor and Tunes Pop" campaign in increasing brand awareness and brand engagement. The study employed a descriptive approach through a practical communication project by implementing Integrated Marketing Communication (IMC), social media management, collaboration with micro influencers, and interactive programs such as Vote Your Iftar Flavor and Ramadhan Satnight Tunes. The author served as Marketing Communication, Social Media Specialist, and Data Analyst. The results showed an increase in social media reach, audience interaction, and consumer participation. Overall, the campaign successfully increased brand awareness and brand engagement while strengthening Mami Ayam Pop's positioning as an Ayam Pop specialist in Semarang City.